The Existence of The MPR Post Amendment to The 1945 Constitution Related to he Representative System in Indonesia - Freddy Poernomo (UIN Sunan Gunung Djati, 2022)
Based on articel (2) point (1) the 1945 Constitution after reconstruction state that General Poeple Assembly consist of members from House of Representative and Regional House of Representative. According from this fact that General People Assembly is independent institution or organisation besides House of Representaive dan Regional House of Represntative. It’s consequensi that have three representative organ in Indonesia. Therefore General People Assembly is independent institution but don’t have legislative authority. There is deferent fact between House of Representaif and Regional House of Representative Authority.